Evaluation of heavy metal concentration in wild and cultivated Hemibagrus sp. using principal component analysis - Nor Shahirul Umirah Idris; Sharifuddin Md.Zain; Kah Hin Low; Ahmad Firdaus Kamaruddin; Kaharudin Md. Salleh (The Malaysian Analytical Sciences Society, 2016)
In the present study, the concentration of Cr, Cd, Cu, Zn, Pb, and As in various tissues of Hemibagrus sp. from two different habitat were determined with microwave assisted digestion-inductively coupled plasma-mass spectrometry. The objective of this research was to determine the differences between wild and cultivated in terms of heavy metal accumulation in muscle, liver and gills tissues. The metals accumulation pattern relating types of tissue and elements as well as fish habitats were revealed by principal component analysis. The results revealed that variation in metal accumulation pattern is strongly dependent on the type of tissues. The results suggested that Cu, Zn, and Pb are highly associated with liver tissue while Cr and As with muscle and gills. The differences in heavy metal accumulation observed between wild and cultivated Hemibagrus sp. were probably due to the differences in their environmental conditions.